IMPLEMENTASI MANAJEMEN KURIKULUM DALAM MENINGKATKAN MUTU PENDIDIKAN DISEKOLAH DENGAN SUMBER DAYA TERBATAS DI SMP YAPIMDA PLUS JAKARTA - Melly Aprilliyanti; Siti Nurhasanah (Sekolah Tinggi Ilmu Tarbiyah Togo Ambarsari, 2026)
Curriculum management is a strategic instrument in determining the direction of educational quality; however, its effectiveness is often hindered by the limited structural resources in private schools. This study aims to analyze the implementation of curriculum management functions, including planning, development, implementation, and evaluation, and its impact on educational quality. The research employs a qualitative approach with a descriptive method. Data collection was conducted through in-depth interviews, observations, and document studies. The findings reveal that curriculum management is carried out through a pragmatic-adaptive approach as a response to the lack of facilities and competencies. Planning and development are carried out through benchmarking strategies and partial modifications to address the scarcity of professional training. Implementation relies heavily on teacher agency with dual job responsibilities and social capital based on familial ties, yet is distorted by low external participation. Evaluation has shifted its orientation from pedagogical substance to administrative concerns, with the adoption of compensatory assessment mechanisms based on character development to support students' academic progress. The significance of this research lies in its contribution to understanding how curriculum management, adapted to resource constraints, can still ensure the sustainability of quality education in private schools, providing valuable insights for other similar institutions facing comparable challenges.